A compact, high isolation building block for 8 × 8 multi‐input multi‐output antenna array suitable for 5G smartphone applications. Issue 12 (22nd October 2022) - Gupta, Surendra Kumar; Bage, Amit; Ranjan, Pinku
Abstract: In this article, compact inverted F‐antennas (IFAs) operating in the 3.5 GHz band is proposed for future 5G smartphone applications. The conventional IFA is modified to make the structure compact and efficient. The additional IFAs are aligned in face‐to‐face configuration to reduce the coupling between them up to some extent. Furthermore, a novel decoupling element is incorporated between antenna pairs to effectively enhance the isolation. As a result, the proposed building block exhibits isolation higher than 28.2 dB between two adjacent ports. Based on highly isolated building blocks, a 4 × 4 and 8 × 8 multi‐input multi‐output (MIMO) antenna array is designed and investigated which is operated in 3.5 GHz (LTE band 42). The proposed 8 × 8 MIMO antenna array has four compact building blocks and reserves sufficient space for integrating other antennas such as 2G/3G/4G antennas. To validate the simulated results, a prototype of the proposed antenna is fabricated and tested. Over the entire operating frequency, the fabricated 8 × 8 MIMO antenna array obtain high isolation of more than 27.3 dB, and high antenna efficiency (>61%). Also, its corresponding measured envelope correlation coefficients are lower than 0.04 and channel capacity was about 39.1–40.6 bps/Hz. The measured results show that the proposed MIMO antenna array is a good candidate for future fifth‐generation smartphone applications.